Grafting of Polyethyleneimines on Porous Silica Beads and Their Use for Adsorptive Removal of Cr(VI) from Aqueous Medium - Ayane Taki; Kouta Morioka; Keiko Noguchi; Hiromichi Asamoto; Hiroaki Minamisawa; Kazunori Yamada (Physchem, 2024)
Porous silica-based adsorbents for hexavalent chromium (Cr(VI)) ion removal were prepared by the combined use of functionalization with (3-glycidyloxypropyl)trimethoxysilane and the grafting of branched and linear polyethyleneimine (BPEI and LPEI). LPEI was prepared from polyethyloxazolin by hydrolysis with HCl. The preparation of LPEI was identified by NMR measurements and the grafting of BPEI and LPEI on the silica beads was confirmed by an XPS analysis. The Cr(VI) ion adsorption of the obtained BPEI-grafted silica beads (BPEI–silica beads) was investigated as a function of the pH value, the content of amino groups, the temperature, the Cr(VI) ion concentration, and the molecular mass of the grafted BPEI chains. The Cr(VI) ion adsorption at pH 3.0 increased with an increase in the content of amino groups, and the maximum adsorption capacity of 1.06 mmol/g was obtained when the content of amino groups was at 2.17 mmol/g. This value corresponds to 589 mg/g−1.8KPEI, and the adsorption ratio of about 0.5 is a noteworthy result. The data fit to the pseudo-second-order kinetic model, and the suitability of this fitting was supported by the results that the adsorption capacity and initial rate of adsorption increased with the temperature. In addition, the equilibrium data followed the Langmuir isotherm model. These results clearly demonstrate that the Cr(VI) adsorption occurred chemically, or through the electrostatic interaction of protonated amino groups on the grafted BPEI chains with hydrochromate (<semantics><msubsup>HCrO4−</msubsup></semantics>) ions. A higher adsorption capacity was obtained for the silica beads grafted with shorter BPEI chains, and the adsorption capacity of BPEI–silica beads is a little higher than that of linear PEI-grafted silica beads, suggesting that the Cr(VI) ion adsorption is affected by the chain isomerism of PEI (linear and branched) as well as the molecular mass of the grafted PEI chains, in addition to the content of amino groups. The experimental and analytical results derived from this study emphasize that the BPEI–silica beads can be used as an adsorbent for the removal of Cr(VI) ions from an aqueous medium.